Assessment of Water Quality of Tigris River by using Water Quality Index (CCME WQI) - Al-Janabi, Zahraa Zahraw; Al-Kubaisi, Abdul-Rahman; Al-Obaidy, Abdul-Hameed M Jwad (Al-Nahrain Journal of Science, 2018)
The present work describes the application of Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) for the 3 stations located along with Tigris River in Baghdad city, Iraq. The field work was conducted during the period from February to December 2010. CCME WQI was applied using eleven water quality parameter (pH value, Total Dissolved Solids, Calcium, Total Alkalinity, Ammonia, Nitrate, Nitrite, Turbidity, Lead Chromium, Iron). Based on the results obtained from the index, the water quality of Tigris River ranged between 37-42 which indicate that river has the worst quality due to effect of various urban pollutant sources. This work confirms the need to take a serious action for monitoring the river for proper management.